Impact Resistance of Complex 3D‐Printed Schwarzites Structures - Ambekar, Rushikesh S.; Oliveira, Eliezer F. [UNESP]; Pugazhenthi, Piraisoodan; Singh, Shatrughan; Mahapatra, Debiprosad Roy; Galvao, Douglas S.; Tiwary, Chandra S. (Wiley, 2025)
Schwarzites are 3D carbon allotropes with negative Gaussian curvatures. Herein, the ballistic impact resistance and structures experimentally and energy‐absorption capabilities of schwarzites from the gyroid and primitive families are investigated. Atomic and their corresponding 3D‐printed structural models are investigated. In the schwarzite family, Ω 2 and Ψ 2 have sustained the impact with minimal damage. The tested structures are further scanned using computer tomography to reveal and investigate their internal damage features. Molecular dynamics simulation results are in good agreement with the impact tests of the 3D‐printed structures, suggesting that the mechanical properties are determined mainly by the topological features and are scale‐independent. The results point out that the performance of schwarzites structures is related to their local curvature, i.e., their flatness due to their ratio of hexagons to octagons. In general, the lower the ratio of hexagons to octagons, the stiffer the structure. Controlled mechanical response is possible by designing hierarchical schwarzite structures, making these structures good candidates for applications requiring lightweight materials with high resistance to ballistic impacts.